Pregnancy outcomes in non-gynecological and non-hematological cancers: a retrospective cohort - Kumari, Minakshi; Yenuberi, Hilda; Rathore, Swati; Abraham, Deepak; Titus, V. T. K.; Mathews, Jiji Elizabeth; Singh, Ashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Of all the cancers in women, about 10% manifest in the reproductive age group. These can be broadly classified as gynaecological cancers and non-gynaecological cancers; Among the non-gynaecological cancers besides haematological cancer, breast, thyroid, colon, bone and CNS are seen rarely. Clinical acumen in diagnosis and management of these rare cancers that appear during pregnancy or before pregnancy are difficult due to insufficient guidelines and rarity of the conditions. Methods: A retrospective analysis of rare cancers during a period of 10 years in this hospital was performed. Data concerning the gestational age at delivery, birth weight, mode of delivery and complications and the management of the cancers during the pregnancy were collected. Results: Among the 41 women with these rare non-gynecological, non-hematological cancers, 13 pregnancies were in women with prior history of cancers and 28 pregnancies were with current history of cancer. Majority of these cases with prior history were thyroid cancers who had uneventful pregnancies and delivered normally. Among pregnancies with current history of cancer, breast, CNS, GIT, and head and neck were the cancers with 5-6 cancers in each category. About 50% of these cancers were delivered early between 31-35 weeks to facilitate optimal treatment. Cancers with guarded prognosis diagnosed before 20 weeks had a termination of pregnancy. Conclusions: Cancers during pregnancies are rare and their care must be individualized.